The impact of physical activity on self-emotion management among university students in Western China: the mediating roles of self-rated health and life satisfaction - Zhang, Xin-yu; Zhang, Yang-Sheng; Han, Shan-shan; Kuan, Garry; Lou, Hu; Mu, Fan-zheng; Zhu, Wei-dong; Ye, Yu-peng; Li, Ya-xing; Meng, Shu-qiao; Feng, Shuo; Li, Han; et al. (Frontiers in Psychology, 2025)
ObjectiveThis study aims to investigate the impact of Physical Activity on Self-Emotional Management among university students and to verify the mediating roles of Self-Rated Health and Life Satisfaction.MethodsA stratified cluster sampling method was used to enroll 10,300 university students from Western China. Questionnaires were used to collect data, which included demographic and sociological information, the Physical Activity Scale (for measuring Physical Activity), the Emotional Intelligence Scale (for measuring Self-Emotional Management), the Short-Form Health Survey (for measuring Self-Rated Health), and the Satisfaction with Life Scale (for measuring Life Satisfaction). The results were statistically analyzed by using SPSS 26.0.ResultsThere was a positive correlation between different intensities of Physical Activity and Self-Emotional Management among university students in Western China (p < 0.001). Yet the direct predictive effect on Self-Emotional Management was not significant. Low-Intensity Physical Activity positively predicted Self-Rated Health (β = 0.876, p < 0.001), while Vigorous-Intensity Physical Activity negatively predicted Self-Emotional Management (β = −1.500, p < 0.001). Self-Rated Health positively predicted both Life Satisfaction and Self-Emotional Management (β = 0.118, p < 0.001; β = 0.030, p < 0.001), and Life Satisfaction positively predicted Self-Emotional Management (β = 0.403, p < 0.001). Self-Rated Health partially mediated the relationship between Low-Intensity Physical Activity/Vigorous-Intensity Physical Activity and Self-Emotional Management, with effect sizes of 0.026 (95% CI: 0.002–0.052) and −0.045 (95% CI: −0.080 to −0.010) respectively. The serial mediation pathway, the Low-Intensity Physical Activity/Vigorous-Intensity Physical Activity→Self-Rated Health→Life Satisfaction→Self-Emotional Management was significant (p < 0.05).ConclusionLow-Intensity Physical Activity or Vigorous-Intensity Physical Activity cannot directly influence university students’ Self-Emotional Management ability. Based on self-determination theory, Self-Rated Health can independently influence university students’ Self-Emotional Management ability. It can also indirectly influence Self-Emotional Management by incorporating the chained mediation effect of Self-Rated Health and Life Satisfaction.